The Use of Arbitrary Signs in A-Mild Cigarette Advertising: A Ferdinand de Saussure Semiotic Study - Meiyanti Nurchaerani; Pamungkas, Ario; Alfian; Hidayatullah Rizkyka Hartadhi, Syahiid (Journey: Journal of English Language and Pedagogy, 2025)
This study examines the communication strategy used in the Sampoerna A-Mild cigarette advertisement “Solusi Lo, Masalah Buat Gue” within the context of Indonesia’s strict advertising regulations. Employing a qualitative descriptive approach and Ferdinand de Saussure’s semiotic framework, the research analyzes how visual and verbal signifiers such as urban heat, traffic congestion, and the motorcyclists’ actions are linked to signified meanings including frustration, pragmatism, and individual initiative. The findings show that these signs are intentionally connected through arbitrary associations that construct a narrative of resourcefulness and non-conformity. The slogan “Solusi Lo, Masalah Buat Gue” functions as the central linguistic element that unifies the advertisement’s sign system and contributes to an implied identity distinction between individuals who act creatively and those affected by such actions. The study highlights how the advertisement communicates brand identity indirectly, demonstrating how cigarette companies adapt meaning-making strategies to operate within regulatory constraints. These findings expand the understanding of semiotic mechanisms in regulated advertising and show how arbitrary sign-linking serves as a strategic tool for maintaining brand presence without explicit product depiction.